Pelatihan penggunaan aplikasi Inventaris Gudang Puskesmas Sakra - Hamzan Ahmadi; Aris Sudianto; Hadian Mandala Putra; Muhammad Iman Darmawan (Universitas Hamzanwadi, 2021)
An inventory system is a system that manages data on items owned by an office. A good inventory system will help a company manage data on goods owned by the company. Not only do big companies need an inventory system, but small offices also need an inventory system. Likewise, with the Health Center, managing data such as drugs, medical equipment, stationery, etc., requires a good warehouse inventory system. Therefore, this service activity aims to develop and train the Health Center Warehouse Inventory application. The partner of this activity is the Sakra Community Health Center (administrative staff). The methods used are lectures, mentoring, and direct practice using applications. The result of this activity is the production of warehouse inventory system software for the Sakra Health Center. In addition, the Sakra Health Center's administrative staff can also run the software